Il motivo dell’aiuto reciproco fra il cieco e lo zoppo: tecnica della variazione e tradizione intertestuale in Epigr. Bob. 55 e 56 Sp. - D’ANGELO, Rosa Maria (AL. Rivista di studi di Anthologia Latina, 2021)
Abstract The subject of Epigr. Bob. 55 and 56 was developed by the anonymous author not only through the reworking of AP IX 11, 12, 13 and 13b, but also through a transversal tradition which attributed to the apologue of the blind and the lame a theological function in the moral debate on the relationship between soul and body and which included the topic of physical disability among the declamatory exercises. It is likely that Girolamo Avanzi corrected Epigr. Bob. 65, 2 under the influence of the philosophical and rhetorical tradition.